การประยุกต์ใช้ทุนทางสังคมกับการจัดการทรัพยากรธรรมชาติ: กรณีศึกษาป่าชุมชนบ้านห้วยสะพานสามัคคี ตำบลหนองโรง อำเภอพนมทวน จังหวัดกาญจนบุรี - ชำนาญกิจ, บัณฑิตา (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 25 No 2 (2557): Academic Services Journal, Prince of Songkla University, 2014)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาทุนทางสังคมที่ปรากฏอยู่ในชุมชนบ้านห้วยสะพานสามัคคี 2) ศึกษาการประยุกต์ใช้ทุนทางสังคมกับการจัดการทรัพยากรธรรมชาติของชุมชนกรณีป่าชุมชนบ้านห้วยสะพานสามัคคี ดำเนินการศึกษาโดยใช้กระบวนการวิจัยเชิงคุณภาพเป็นหลัก โดยอาศัยกระบวนการและวิธีการสัมภาษณ์แบบเจาะลึกกับผู้ให้ข้อมูลที่สำคัญ จำนวน 15 ราย ร่วมกับการใช้การสังเกตการณ์และการศึกษาทบทวนวรรณกรรมจากเอกสาร รวมทั้งใช้การตรวจสอบความถูกต้องของข้อมูลด้วยเทคนิคสามเส้า และทำการวิเคราะห์ด้วยการจำแนกหมวดหมู่ พิจารณาความสอดคล้องของเนื้อหา โดยยึดหลักตรรกะเทียบเคียงกับแนวคิดทฤษฎีควบคู่กับบริบทของชุมชน ผลการวิจัยพบว่า 1. ทุนทางสังคมที่ปรากฏอยู่ในชุมชนบ้านห้วยสะพานสามัคคีประกอบด้วย 1) มิติของความรู้ ได้แก่ องค์ความรู้/ภูมิปัญญา และศักยภาพของคนและผู้นำ 2) มิติของความดี ได้แก่ บรรทัดฐานทางสังคม วัฒนธรรม ประเพณี และความเชื่อทางสังคม และ 3) มิติของความรัก ได้แก่ ความไว้วางใจ ความเอื้ออาทรต่างตอบแทน ช่วยเหลือกัน และสถาบันทางสังคมและเครือข่ายทางสังคม จากการวิจัยพบว่า ทุนทางสังคมที่เด่นชัดที่สุดอันดับ 1 ของชุมชนบ้านห้วยสะพานสามัคคี อยู่ในมิติของความรัก คือ เครือข่ายทางสังคม อันดับ 2 อยู่ในมิติของความดี คือ บรรทัดฐานสังคม และอันดับ 3 อยู่ในมิติของความรู้ คือ ศักยภาพของคนและผู้นำ 2. การประยุกต์ใช้ทุนทางสังคมหรือขับเคลื่อนไปสู่สังคมที่พึงปรารถนามีขั้นตอน ดังนี้ 1) การรับรู้และตระหนักถึงปัญหา 2) การทดลองริเริ่มให้เกิดความเปลี่ยนแปลง 3) การวางแผนและกำหนดเป้าหมาย 4) การรวมกลุ่มสร้างเครือข่าย 5) การระดมทุน 6) การลงมือทำ และ 7) การสรุปและประเมินผล ในการขับเคลื่อนกระทำผ่านชุดกิจกรรมโดยอาศัยทุนในสังคมที่มีอยู่ในชุมชน คือ ทรัพยากรป่าชุมชน ซึ่งจากการวิจัยพบว่า ระดับของการประยุกต์ใช้ทุนทางสังคมของชุมชนบ้านห้วยสะพามมี 3 ระดับ ได้แก่ 1) ระดับเพื่อให้เกิดประโยชน์ต่อชีวิตและครอบครัวของตนเอง 2) ระดับเพื่อให้เกิดประโยชน์ต่อกลุ่มหรือเครือข่าย 3) ระดับกลุ่มหรือเครือข่ายการพัฒนาชุมชน ข้อเสนอแนะจากการวิจัย 1) การจัดการทุน คณะกรรมการดูแล ป่าชุมชนจะมีการวางแผนบริหารจัดการเพื่อให้มีงบประมาณเพียงพอที่จะเป็นเงินทุนสำรองไว้ใช้ หรือจัดกิจกรรม หรืออาจจะเป็นการสร้างผลกำไรจากการออมทรัพย์ เพื่อนำมาใช้บริหารจัดการป่าชุมชนก็จะช่วยให้มีความยั่งยืนในการจัดการป่าชุมชนได้มากขึ้น และ 2) การถ่ายทอดความรู้ ควรเปิดโอกาสในการสร้างผู้นำรุ่นใหม่ และเปิดโอกาสให้ผู้นำได้ลงมือปฏิบัติงานร่วมกับคนรุ่นเก่าได้ซึมซับความรู้และเทคนิควิธี รวมถึงเกร็ดความรู้จากคนรุ่นเก่ามาประยุกต์ในการถ่ายทอดความรู้ รวมถึงการใช้ประโยชน์จากป่าชุมชนได้คุ้มค่าและยั่งยืนมากขึ้น The objectives of this study are 1) to study social capital which appears in Banhoaisaphan-samakkhi Community; 2) to study the application of social capital to natural resource management of a community, a case study of Banhoaisaphan- samakkhi Community Forest. This study is conducted mainly by qualitative research process and in-depth interview with 15 important information providers together with the observation and the literature review from documents. Also, the accuracy of the information is verified by data triangulation. The analysis is done by the  classification and consideration of content consistency based on the logical principle in comparison with concepts, theories as well as community contexts. The results of the study demonstrate that: 1. The social capital that appears in Banhoaisaphan-samakkhi Community  consists of 1) the knowledge dimension which comprises body of knowledge, wisdom and potentiality of people and leaders; 2) the goodness dimension which comprises social norm and social culture, traditions and beliefs as well as 3) the love dimension which comprises trust, reciprocal generosity as well as social institution and social network. According to the research, the most outstanding social capital of Baan HuaySapanSamakke Community is the love dimension, i.e., social network, followed by the goodness dimension, i.e, social norm and the knowledge dimension, i.e., potentiality of people and leaders. 2. The application of social capital or the movement towards desirable society consists of the following steps: 1) to perceive and realize the problem;  2) to experiment in order to bring about changes; 3) to plan and specify goals; 4) to gather and create a network; 5) to gather capital; 6) to take action and 7) to conclude and evaluate. The movement has been conducted through an activity set with the help of social capital inside the community which is the community forest. The research demonstrates that there are 3 levels of the application of social capital of Banhoaisaphan-samakkhi Community, which are: 1) the level for the benefit of personal lives and families; 2) the level for the benefit of groups or networks and 3) the level for the community development groups or networks.  The suggestions from the research are: 1) in terms of capital management, the committee who takes care of the community forest should have a management  plan in order to put aside sufficient capital for the use of the community or the organization of activities. It is also possible to generate profits from saving for the community forest management for greater sustainability of community forest  management and 2) in terms of knowledge distribution, there should be an  opportunity to create the new generation of leaders and to let them cooperate  with the old generation. The knowledge, techniques, methods and anecdotes from the old generation will be applied in the knowledge distribution. Also, the community forest will be utilized more worthily and sustainably.